Electronic properties and transistors of the NbS2–MoS2–NbS2 NR heterostructure. (11th January 2017) - Liu, Qi; Ouyang, Fangping; Yang, Zhixiong; Peng, Shenglin; Zhou, Wenzhe; Zou, Hui; Long, Mengqiu; Pan, Jiangling
Abstract: Based on density function theory and nonequilibrium Green's functions, we construct a NbS2 –MoS2 –NbS2 NR inplane heterostructure. The effects of channel length, width, chirality and vacancy of the heterostructure on transport properties are systematically investigated. The electron transport of the armchair-edge heterostructure device shows ballistic transport properties, while the zigzag-edge heterostructure device exhibits resonance tunneling transport properties. Further study indicates NbS2 –MoS2 –NbS2 field effect transistors (FETs) to be excellent ambipolar transistors. The FETs have high performances with current on/off ratio 4.7 × 10 5 and subthreshold swing 90 mV/decade with channel length m = 16 and width n = 6. Increases in the channel length sharply reduce the off-state current and enhance the performance of the devices significantly.